URGENT MEASURES IN OVERCOMING A CRISIS IN A COMPANY - Branko Mihailović; Drago Cvijanović (Economic Review)
In many organizations in Serbia a crisis can be seen, which manifests through decrease of market share and profitability, increased indebtedness, inadequate investment and multiplication of new business projects at the expense of a primary business. The crisis symptoms are characterized by mainly ex post pointing at the situation in a company. Consequentially, the aim of the paper is to define adequate urgent measures, which would lead to improvement of company's business performances. In the realization of a research task, a desk research was used of the data, which refer to indicators of company performances in Serbia. Such research implies using data from the official resources: international organizations' resources; data from domestic and foreign literature; and internal data base of the Institute of Agricultural Economics, Belgrade. For years, companies in Serbia have functioned on nonmarket principles. It led to increased lagging behind of domestic economy in regard to the market principles. It turned out that the partial changes, without an encroachment on the proprietary structure and prevailing ownership relation, do not lead to increase in business efficiency. But, increasing competition and claims for business success have motivated the companies in Serbia to apply market business principles. Transforming the ex-socialist economies into the market ones represents a process of transition, which creates a new business environment and new institutional infrastructure. Adjusting to the new business environment is realized through a restructuring process, which aims to improve company’s business performances.